PENGEMBANGAN MANAJEMEN KESISWAAAN DALAM MENINGKATKAN MINAT DAN BAKAT SISWA DI SEKOLAH DASAR ISLAM ROUSHON FIKR JOMBANG - Ahmad Nur Ismail; Ahmad Nur Ismail; Achmad Chomaidi Alwi; Mochammad Fuad Habib (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2021)
This research aims to find out the student management process which includes planning, organizing, implementing and evaluating in student management at Islamic Elementary School (SD Islam) Roushon Fikr Jombang. This study uses qualitative approach with qualitative descriptive research type. Data collection techniques in this study using interview methods, observations and documentation. The results showed that the planning of students at SD Islam Roushon Fikr Jombang is a student management planning program prepared by the deputy principal III in the field of student affairs in the plenary session to the foundation by adjusting the needs and following the development of the school. The development of students at SD Islam Roushon Fikr Jombang is done such as instilling a responsible attitude such as coaching discipline given by the student. The development of extracurricular activities at SD Islam Roushon Fikr Jombang is carried out by providing special guidance and training in accordance with their fields to strengthen the skills and interests of students' talents. Evaluation of students' learning is done to see the success and improve the activities that have been carried out.